The Prevelance of Hepatitis B Surface Antigen (HBsAg) Among Blood Donors in Some Hospitals of Thamar, Yemen - Al-Alousi, Maha; Al-Makdad, Abdulsalam; Al-Jarfi, Arafat (Thamar University Journal of Natural & Applied Sciences, 2023)
Viral hepatitis is a general term meaning inflammation of the liver and can be caused by a variety of viruses such as hepatitis B virus.Hepatitis B is a serious transfusion-transmissible disease affecting millions of people throughout the world.This study was designed to evaluate the prevalence of HBsAg and the risk factors for HBV infection among blood donors in Thamar governorate/Yemen, and to focus upon the importance of blood transfusion in spreading the hepatitis B virus.A total of 200 blood donors at the blood bank of Thamar hospital and Al-Wehda teaching hospital, during the period of January 2009 to October 2009, and January 2010 to July 2010, were screened for the presence of hepatitis B surface antigen (HBsAg) . Each patient filled a questionnaire including age, sex, dental visit, blood transfusion ..etc. The donors were all male adult (age: 17-45 years).Four out of 200 (2%) donors were found to be HBsAg positive by an enzyme-linked immunosorbent assay (ELISA) using monoclonal antibodies to HBsAg. Two of the four (50%) HBsAg-positive donors have relative symptoms of HBV (i.e jaundice) while the other two HBsAg-positive donors were asymptomatic. Questionnaires revealed that: The four positive donors were all married. The two asymptomatic HBsAg-positive donors were army soldiers. The other two symptomatic donors were civil workers.One of the two asymptomatic donors has donated a blood a year ago and found to be HBsAg negative.One of the symptomatic positive donors has had two previous surgical operations and received several pints of blood.This study emphasizes the need for an accurate detection of this virus, and the need for using confirmatory tests for HBsAg detection and also the need to undertake serious measures to control the spread of HBV among Yemeni people.